(untitled) (De Rebus Antiquis, 2021)
According to a general opinion, based on Libanius’Orations, the emperor Julian (361-363 CE) reduced the number and power of the imperial notarii. However, there is no other evidence of a reform concerning the notarii. Furthermore, a prosopographical research suggests that they were ‘special agents’ also under Julian and some of them were promoted by him to the highest offices. The aims of this paper is, therefore, to question the current interpretation, by comparing Libanius’Orations with the other sources on Julian’s court reform. Special attention is also given to Libanius’representation of the imperial court and his use of the word á½‘Ï€Î¿Î³ÏÎ±Ï†Îµá¿–Ï‚ whose meaning can not be limited to the imperial notarii.